Non-Government Organization (NGOs) in Bangladesh: a study of their role in participatory rural development - Quddus, S. M. Abdul (The Academy for Planning and Development, 1995)
This is about NGO intervention in the development of rural sector. The issue of participation is discussed with a good deal of emphasis. The study seeks to point up the NGO plans of action in activating the involvement of the target beneficiaries. Promoting participatory development has much to do with the process of conscientisation so that the beneficieries could be able to use their own potentials of self development pruning of all evil dependency. The phenomenon of NGO activism in promoting human values in participatory stratagy is analized with reference to the development activities of a couple of operating NGOs. Most NGOs appear to approach the problem of development with crush schemes. Yet the flexibility inherent in NGO model is capable of producing result in term of awareness building, group formation, employment generation and credit disburstment. NGO promotional agencies have perform well in effectively rendering extension services compared to the public promotional agencies. They reach out to the people specially the rural poor. Realizing the need for sustainability of institutional development some NGOs are begining to rethink in hard lines. This is considered worstwhile at this critical juncture as poverty issue arising out of growth model in gaining prominence.